Interplay of upper and lower motor neuron degeneration in amyotrophic lateral sclerosis. Issue 11 (November 2017) - de Carvalho, Mamede; Poliakov, Artiom; Tavares, Cristiano; Swash, Michael
Highlights: Variability of recruited motor units can be estimated by using mean consecutive differences (MCD) MCD is reduced in patients with marked upper motor neuron involvement. This tool can be developed for clinical application. Abstract: Objective: We studied motor unit recruitment to test a new method to identify motor unit firing rate (FR) variability. Methods: We studied 68 ALS patients, with and without upper neuron signs (UMN) in lower limbs, 24 patients with primary lateral sclerosis (PLS), 13 patients with spinal cord lesion and 39 normal subjects. All recordings were made from tibialis anterior muscles of normal strength. Subjects performed a very slight contraction in order to activate 2 motor units in each recording. 5–7 motor unit pairs were recorded in each subject. Mean consecutive differences (MCD) were calculated for each pair of potentials. The mean MCD for each muscle was estimated as the mean from the total number of pairs recorded. A p value < 0.01 was accepted as significant. Results: MCD of FR frequency was less in the subjects with spinal cord lesion and PLS. In addition, the FR frequency of the 1st motor unit in a pair of units was markedly reduced in PLS, and in subjects with spinal cord lesions. Conclusion: These results support a lower threshold and reduced FR fluctuation in spinal motor neurons of spastic patients. Significance: This method can be developed for detection of UMN lesions.